Development of Islamic Values–STEM Integrated Instructional Materials to Enhance Students’ Analytical Thinking Skills - amrullah, amrullah; Syauqi Alfanzari, Achmad; Wiranata, Erik; Hastuti, Miryana (LPPM Universitas Ibn Khaldun, Bogor, 2026)
This study set out to design and refine instructional materials for Islamic Educational Philosophy by weaving together Islamic values and a STEM-oriented perspective, with the broader aim of strengthening students’ analytical thinking. The project followed a Research and Development (R&D) approach and adopted the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation). It was carried out in the Graduate Program of IAIN Curup. The initial needs assessment revealed a rather telling pattern. Around 83.33% of lecturers and 85.45% of students felt that the existing teaching materials did not fully respond to the demands of current learning practices. In other words, there was a clear gap between what was available and what was actually needed in the classroom. After the materials were developed and reviewed, they achieved an average validity score of 92.03, which places them in the “highly appropriate” category. The product was considered ready for implementation without substantial revision. From the students’ perspective, the response was equally encouraging: all participants (100%) rated the materials as appropriate or highly appropriate for use, suggesting a strong level of practicality and perceived effectiveness. More importantly, the integration of Islamic values with a STEM framework appeared to sharpen students’ analytical capacities. They showed greater confidence in interpreting philosophical issues, constructing coherent and logically grounded arguments, and connecting ethical reasoning with scientific modes of inquiry. Taken together, these findings indicate that thoughtfully designed integrative materials can do more than deliver content, they can reshape the way students think. Keywords: Islamic Educational Philosophy, Islamic Values–STEM Integration, Analytical Thinking, Instructional Materials